Colégio Lourdinas da capital Paraibana: um modelo educacional para um público feminino Pessoense (1939-1999) - Pinheiro, Danielle Ventura de Lima (2018)
The Lourdinas school of João Pessoa-PB appeared in the year of 1939. In 1999 the institution exclusively attended the female public. Of Catholic kind, the institution had during all those years the nuns in is direction. Going through changes in its physical and pedagogical structure over the years, the Lourdinas school has sought to adapt to the needs of its time without ceasing to bring with it some permanences that are peculiar to it, such as the emphasis on Marian education and behavioral rigidity. To understand this school daily that involves a feminine Catholic teaching were carried out documentary analyzes and of the speeches present in school diaries, notebooks, foundation report, testimony of former students and teachers, which allowed not only observe the school practices, but as the school is seen by the former students, who now resist the rules of behavior and now bring back memories. The studies of concepts such as traditional education, school daily life, school institution and memory, in the light of theorists who turn to the school space itself and authors like Halbwach (2006), Hobsbawn (2006) and Foucault, were fundamental to guarantee the understanding of this school institution never studied before in other academic work. As results, one can consider that the institution has this profile to satisfy to its public, being able to make some modifications so that it is appropriate to the reality, as well as it is possible to perceive the resistance of some and the institutional rigor between the lines of the speeches of her former students.